Biomass production, root colonization and phosphatase activity by six VA-mycorrhizal fungi in papaya - M. RANGARAJAN, Z. JOHN KENNEDY and (Indian Phytopathology, 2002)
Six VA-mycorrhizal fungi were tested for their ability to increase the biomass by colonization of roots and phosphatase activity in three varieties of papaya (Carica papaya L)_ Among the six VA- mycorrhizal fungi, Glomus mosseae was most effective in increasing the shoot and root dry weight over control. The per cent increase of shoot and root dry weight varied from 30.2 and 49.34 in CO 2 variety, 46.51 and 40.43 in CO 5 variety and 62.45 and 26.68 in 9-1 D variety on 90 days after sowing (DAS). The root colonization per cent was high in Glomus mosseae inoculated plants followed by G. fasciculatum, Acaulospora longula, G. claroideum, G. geosporum and A. laevis irrespective of the varieties of papaya. Among the varieties of papaya, CO 5 recorded maximum root colonization followed by CO 2 and 9-ID varieties irrespective of VAM fungi. Phosphatase activity due to mycorrhizal colonization showed that both the acid and alkali phosphatase activity increased significantly in all the three varieties of papaya. Acid phosphatase activity was higher than alkali phosphatase activity. Nutrient content of N,P and K and also of Fe, Mn, Zn and Cu increased due to VAM inoculation. Among the VAM species, G. mosseae recorded maximum N,P and K content of 1.84, 0.35 and 1.95 per cent in CO 5, 1.75,0.33 and 1.80 per cent in CO 2 and 1.75, 0.29 and 1.70 per cent in 9-1 D variety respectively.